Synthesis and fungicidal activity of novel 2-aryl-3-(1,3,4-thiadiazolyl)-6(8)-methyl-1,3-benzoxazines - Tang, Zi-long; Xia, Zan-wen; Chang, Shu-hong; Wang, Zhao-xu (Bioorganic & medicinal chemistry letters, 2015)
[Display omitted] A class of novel 2-aryl-3-(1,3,4-thiadiazolyl)-6(8)-methyl-1,3-benzoxazines was prepared by reactions of 2-methyl-6-((1,3,4-thiadiazolylamino)methyl)phenols or 4-methyl-2-((1,3,4-thiadiazolylamino)methyl)phenols and 2- or 4-nitrobenzaldehyde in the presence of TMSCl in refluxing toluene. The electron-donating methyl group on the benzene ring played an essential role on the reactivity of the substituted phenols, which was proved by DFT calculation. The fungicidal activity of the resultant products were also preliminarily evaluated, most of which displayed moderate to good fungicidal activity. Especially, compound 6f showed 98.0% activity against Sclerotonia sclerotiorum and Botrytis cinerea at concentration of 25μg/mL.